Method for treating lanthanum residue

CN119710313BActive Publication Date: 2026-10-30BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510118052.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2026-10-30
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

碳热还原法的原料成本相对低廉,但是在冶炼过程中容易形成高熔点的稀土碳化物,稀土碳化物聚集在炉底形成炉瘤,造成炉底迅速上涨,炉况难以稳定

Benefits of technology

[0065]本发明能够将镧热还原法生成的固废镧渣形成有价的稀土硅铁合金,变废为宝,能够充分地利用稀土资源,极大地降低稀土硅铁合金的制造成本,具有极高的商业价值。本发明的处理方法得到的稀土硅铁合金的纯度高,稀土回收率高。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a treatment method of lanthanum residue. The treatment method comprises the following steps: (1) pre-sintering a blank containing a first carbonaceous reducing agent and lanthanum residue at 400-600 DEG C for 50-120 min to obtain a pre-sintered product; (2) smelting smelting raw materials including the pre-sintered product, a second carbonaceous reducing agent and silica at 1700-2200 DEG C for 3-8 h to obtain an alloy melt; (3) pouring and forming the alloy melt to obtain a rare earth ferrosilicon alloy; wherein the first carbonaceous reducing agent is selected from one or more of coke, semicoke, semi-coke, charcoal, gas coal coke, bituminous coal and petroleum coke; and wherein the second carbonaceous reducing agent is selected from one or more of coke, semicoke, semi-coke, charcoal, gas coal coke, bituminous coal and petroleum coke. The treatment method can form the solid waste lanthanum residue into a rare earth ferrosilicon alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for treating lanthanum slag. Background Technology

[0002] Lanthanum slag is a solid waste remaining after the lanthanum thermal reduction process for rare earth metals, and it contains a large amount of rare earth elements. If these rare earth elements in the lanthanum slag can be reused, costs will be greatly reduced, and rare earth resources will be fully utilized.

[0003] Rare earth ferrosilicon alloys are widely used in metallurgy, casting, machinery, and military industries. The main production methods for rare earth ferrosilicon alloys are the silicothermic reduction method, carbothermic reduction method, molten salt electrolysis method, and smelting method. The silicothermic reduction method and carbothermic reduction method have become the mainstream methods for large-scale industrial production due to their high production efficiency and large production volume. The silicothermic reduction method first involves smelting ferrosilicon in an electric furnace, then using ferrosilicon as raw material, adding rare earth materials and calcium oxide for co-smelting to obtain the rare earth ferrosilicon alloy. This process has disadvantages such as low rare earth element recovery rate, large amount of solid waste slag, and high residual rare earth content in the slag. The carbothermic reduction method uses rare earth concentrate, silica, and carbonaceous reducing agents as raw materials, and continuously smelts rare earth ferrosilicon alloys in a submerged arc furnace. The raw material cost of the carbothermic reduction method is relatively low, but it easily forms high-melting-point rare earth carbides during the smelting process. These rare earth carbides accumulate at the furnace bottom, forming furnace nodules, causing the furnace bottom to rise rapidly and making furnace conditions unstable. Furthermore, the carbothermic reduction method has poor stability. Summary of the Invention

[0004] The purpose of this invention is to provide a method for treating lanthanum slag, which can transform solid lanthanum slag into rare earth ferrosilicon alloys. Furthermore, the rare earth ferrosilicon alloys obtained by the method of this invention have high purity. Even further, the method of this invention has a high rare earth recovery rate.

[0005] The above objectives are achieved through the following technical solutions.

[0006] This invention provides a method for treating lanthanum slag, comprising the following steps:

[0007] (1) The green body containing the first carbonaceous reducing agent and lanthanum slag is pre-calcined at 400-600℃ for 50-120 min to obtain the pre-calcined product;

[0008] (2) The smelting raw materials, including pre-baked material, second carbonaceous reducing agent and silica, are smelted at 1700-2200℃ for 3-8 hours to obtain alloy melt;

[0009] (3) The alloy melt is cast into a mold to obtain a rare earth silicon-iron alloy.

[0010] The first carbonaceous reducing agent is selected from one or more of coke, semi-coke, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke. Preferably, the first carbonaceous reducing agent is semi-coke.

[0011] The amount of the first carbonaceous reducing agent, based on the fixed carbon content, is 20-30 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag. Preferably, it is 23-27 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0012] Preferably, the pre-calcination temperature is 450–500°C. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0013] Preferably, the pre-calcination time is 50–80 minutes. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0014] The amount of lanthanum slag used can be determined based on the rare earth ferrosilicon alloy produced.

[0015] The second carbonaceous reducing agent is selected from one or more of coke, semi-coke, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke. Preferably, the second carbonaceous reducing agent is semi-coke. The second carbonaceous reducing agent may be the same as or different from the first carbonaceous reducing agent; preferably, the second carbonaceous reducing agent is the same as the first carbonaceous reducing agent.

[0016] The amount of the second carbonaceous reducing agent, based on the fixed carbon content, is 100–180 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag; preferably 120–150 wt%. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0017] Preferably, the smelting temperature is 1800–2000℃. Smelting can be carried out in a submerged arc furnace. The smelting temperature can refer to the temperature at the bottom of the submerged arc furnace. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0018] Preferably, the smelting time is 4 to 6 hours. This helps to reduce the impurity content of the product and improve the rare earth recovery rate.

[0019] In some embodiments, the smelting raw materials consist of a pre-calcined material, a second carbonaceous reducing agent, and silica.

[0020] According to the processing method of the present invention, preferably, the average particle size of the lanthanum slag is 5-30 mm, the average particle size of the first carbonaceous reducing agent is 5-30 mm, the average particle size of the second carbonaceous reducing agent is 5-30 mm, the average particle size of the silica is 40-150 mm, and the diameter of the smallest enclosing sphere of the billet is 100-300 mm.

[0021] More preferably, the average particle size of the lanthanum slag is 15–25 mm.

[0022] More preferably, the average particle size of the first carbonaceous reducing agent is 15–25 mm.

[0023] More preferably, the average particle size of the second carbonaceous reducing agent is 15–25 mm.

[0024] More preferably, the diameter of the smallest enclosing sphere of the blank is 150 to 250 mm.

[0025] In some embodiments, the billet is cylindrical. The diameter of the bottom surface of the billet can be 100–300 mm; preferably 150–250 mm. The height of the billet can be 100–300 mm; preferably 150–250 mm.

[0026] More preferably, the average particle size of the silica is 80–120 mm.

[0027] Controlling the particle size of the raw materials within the above range helps to ensure sufficient reaction between the raw materials.

[0028] According to the processing method of the present invention, preferably, the content of fixed carbon in the first carbonaceous reducing agent is greater than or equal to 80 wt%, and the ash content is less than or equal to 10 wt%.

[0029] The second carbonaceous reducing agent contains a fixed carbon content of ≥80 wt% and an ash content of ≤10 wt%.

[0030] More preferably, the content of fixed carbon in the first carbonaceous reducing agent is 85-90 wt%.

[0031] More preferably, the ash content in the first carbonaceous reducing agent is 3 to 5 wt%.

[0032] The volatile content in the first carbonaceous reducing agent can be 3–15 wt%. In some embodiments, the volatile content is 5–10 wt%.

[0033] The moisture content in the first carbonaceous reducing agent can be less than or equal to 5 wt%; preferably, the moisture content is 1 to 3 wt%.

[0034] The sulfur content in the first carbonaceous reducing agent can be less than or equal to 1 wt%; preferably, the sulfur content is less than or equal to 0.3 wt%.

[0035] More preferably, the content of fixed carbon in the second carbonaceous reducing agent is 85-90 wt%.

[0036] More preferably, the ash content in the second carbonaceous reducing agent is 3 to 5 wt%.

[0037] The volatile content in the second carbonaceous reducing agent can be 3–15 wt%. In some embodiments, the volatile content is 5–10 wt%.

[0038] The moisture content in the second carbonaceous reducing agent can be less than or equal to 5 wt%; preferably, the moisture content is 1 to 3 wt%.

[0039] The sulfur content in the second carbonaceous reducing agent can be less than or equal to 1 wt%; preferably, the sulfur content is less than or equal to 0.3 wt%.

[0040] According to the processing method of the present invention, preferably, the lanthanum slag contains elemental La, La2O3 and rare earth oxides;

[0041] The rare earth elements in the rare earth oxides are selected from one or more rare earth elements other than lanthanum, the content of elemental La is 1-15 wt%, the content of La2O3 is 75-97 wt%, and the content of rare earth oxides is 1-10 wt%.

[0042] More preferably, the content of elemental La is 3-6 wt%, the content of La2O3 is 85-95 wt%, and the content of rare earth oxides is 3-7 wt%.

[0043] According to the processing method of the present invention, preferably, the rare earth element in the rare earth oxide is selected from one or more of samarium, europium, ytterbium, and thulium;

[0044] The lanthanum slag contains less than or equal to 0.01 wt% calcium and less than or equal to 0.01 wt% lithium.

[0045] The lanthanum slag of this invention can be derived from the lanthanum slag produced by the lanthanothermic reduction method for preparing metallic samarium, europium, ytterbium, or thulium. Therefore, the lanthanum slag contains one or more of samarium oxide, europium oxide, ytterbium oxide, and thulium oxide. In some embodiments, the rare earth oxide contained in the lanthanum slag is samarium oxide. In other embodiments, the rare earth oxide contained in the lanthanum slag is ytterbium oxide.

[0046] More preferably, the calcium content and lithium content in the lanthanum slag are less than or equal to 0.005 wt% and 0.005 wt%, respectively.

[0047] According to the processing method of the present invention, preferably, the green body further contains a binder, the binder being selected from one or more of water glass, silica powder, bentonite, pulp, syrup, and plant starch. More preferably, the binder is plant starch. The plant starch can be corn starch.

[0048] According to the processing method of the present invention, preferably, the adhesive is used in the form of a colloid formed by mixing it with water.

[0049] In some embodiments, the billet consists of lanthanum slag, a first carbonaceous reducing agent, a binder, and water.

[0050] The colloid serves to bind the lanthanum slag and the first carbonaceous reducing agent together to form a green body. The amount of colloid used can be determined as needed. In some embodiments, the amount of colloid used can be 0.5% to 8% of the total mass of the lanthanum slag and the first carbonaceous reducing agent; preferably 2% to 5%.

[0051] In some embodiments, the method further includes the following steps: mixing lanthanum slag, a first carbonaceous reducing agent, and a colloid to obtain a mixture; pressing the mixture into a shape to obtain a green body.

[0052] The silica of the present invention contains 97 wt% or more SiO2; preferably, the SiO2 content is 99 wt% or more.

[0053] The amount of silica used can be determined based on the resulting rare earth ferrosilicon alloy.

[0054] In the processing method of this invention, step (2) can be operated continuously. This ensures continuous production. During continuous production, the material feeding can be adjusted according to the furnace output rate. During continuous production, the furnace can be tamped with an iron or steel tamping rod every 6 to 8 hours.

[0055] According to the processing method of the present invention, preferably, it further includes the following steps:

[0056] The flue gas generated during the smelting process is treated to remove dust, and the dust in the flue gas is collected.

[0057] These dust particles are silicon powder, which can be used to manufacture cosmetics, high-purity silicon, and other products.

[0058] In some embodiments, the smelted alloy melt can be allowed to stand, allowing the slag to float to the surface before casting. The standing time can be 5–30 minutes; preferably 10–20 minutes.

[0059] In some embodiments, the following step is also included: breaking the cast alloy ingot into blocks to obtain a rare earth ferrosilicon alloy.

[0060] According to the processing method of the present invention, preferably, the rare earth element content in the rare earth ferrosilicon alloy is 20-35 wt%, and the total content of silicon and iron is 65-80 wt%.

[0061] More preferably, the rare earth element content in the rare earth ferrosilicon alloy is 25-30 wt%, and the total content of silicon and iron is 70-75 wt%.

[0062] According to the processing method of the present invention, preferably, the content of lanthanum in the rare earth ferrosilicon alloy is 17-32 wt%, the content of silicon is 45-65 wt%, and the content of iron is 12-30 wt%.

[0063] More preferably, the content of lanthanum is 22-27 wt%, the content of silicon is 50-55 wt%, and the content of iron is 16-23 wt%.

[0064] In rare earth ferrosilicon alloys, the content of rare earth elements other than lanthanum can be 1 to 5 wt%; preferably 2 to 3.5 wt%.

[0065] This invention enables the transformation of solid lanthanum slag generated by the lanthanum thermal reduction method into valuable rare earth ferrosilicon alloys, turning waste into treasure. It fully utilizes rare earth resources, significantly reduces the manufacturing cost of rare earth ferrosilicon alloys, and possesses extremely high commercial value. The rare earth ferrosilicon alloys obtained by the processing method of this invention have high purity and high rare earth recovery rate. Detailed Implementation

[0066] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0067] The testing method is described below:

[0068] Chemical composition of lanthanum slag:

[0069] The lanthanum slag was ground and oxidized and roasted in air at 850℃ for 2 hours. The weight gain of the product was measured, and the corresponding weight gain of metallic lanthanum was calculated using the molecular formula of La₂O₃ to determine the mass of elemental lanthanum in the lanthanum slag. Other components were determined by ICP analysis.

[0070] Chemical composition of semi-coke:

[0071] The tests were conducted according to the methods specified in GB / T 25211-2023 Classification and Quality Requirements for Semi-coke Products.

[0072] Chemical composition of rare earth ferrosilicon alloy:

[0073] The tests were conducted according to the methods specified in GB / T 4137-2024 Rare Earth Ferrosilicon Alloys.

[0074] Rare earth recovery rate: (total weight of rare earth in rare earth ferrosilicon alloy / total weight of rare earth in lanthanum slag) × 100%.

[0075] The raw materials are described below:

[0076] The chemical composition of semi-coke is shown in the table below:

[0077] 86.13 <0.3 4.02 7.64 1.91

[0078] The chemical composition of the lanthanum slag obtained from the lanthanum thermal reduction method for preparing samarium is shown in the table below:

[0079] 87.36 5.72 6.64 <0.005 <0.005

[0080] The chemical composition of the lanthanum slag obtained from the lanthanum thermal reduction method for preparing ytterbium is shown in the table below:

[0081] 92.52 3.24 4.23 <0.005 <0.005

[0082] Examples 1-2

[0083] Industrial corn starch is dispersed in water, heated and stirred until it gelatinizes, then diluted with water to form a colloid.

[0084] Lanthanum slag with an average particle size of 20 mm and first semi-coke with an average particle size of 20 mm were mixed, and then mixed with a colloid to obtain a mixture. The amount of colloid used was 3% of the total mass of lanthanum slag and first semi-coke. Based on fixed carbon, the amount of first semi-coke used was 25 wt% of the theoretical amount required to reduce silica and rare earth oxides in lanthanum slag. The mixture was pressed into cylindrical blanks with a diameter of φ200 mm × 200 mm using a hydraulic press. The blanks were pre-calcined at 450 °C for 60 min to obtain a pre-calcined product.

[0085] Pre-calcined material, second semi-coke with an average particle size of 20 mm, and silica with an average particle size of 110 mm were mixed to obtain smelting raw materials. The smelting raw materials were fed into a submerged arc furnace using a feeding machine and smelted for 5 hours at a furnace bottom temperature of 1800℃ to obtain an alloy melt. Based on fixed carbon, the amount of second semi-coke used was 125 wt% of the theoretical amount required to reduce silica and rare earth oxides in the lanthanum slag. The flue gas generated during the smelting process was treated with dust removal, and the dust in the flue gas was collected.

[0086] The alloy melt is left to stand in an intermediate ladle for 15 minutes to allow the slag to float to the surface, and then poured into an ingot mold to cool, thus obtaining an alloy ingot.

[0087] The alloy ingot was divided and crushed into blocks with an average particle size of 30 mm to obtain rare earth ferrosilicon alloy.

[0088] The sources of lanthanum slag and the rare earth recovery rate are shown in Table 1, and the elemental composition of rare earth ferrosilicon alloy is shown in Table 2.

[0089] Table 1

[0090] Example 1 Lanthanum slag obtained from the lanthanum thermal reduction method for preparing samarium 93.3 Example 2 Lanthanum slag obtained from the lanthanum thermal reduction method for the preparation of ytterbium 94.5

[0091] Table 2

[0092] Example 1 27.36 24.65 2.71 — 52.31 20.33 Example 2 28.18 25.35 — 2.83 53.21 18.61

[0093] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A method for treating lanthanum slag, characterized in that, Includes the following steps: (1) A pre-calcined material is obtained by pre-calcining a green body composed of a first carbonaceous reducing agent, lanthanum slag, binder and water at 400-600℃ for 50-120 min; the lanthanum slag contains 1-15wt% elemental La, 75-97wt% La2O3, and 1-10wt% rare earth oxides, wherein the rare earth elements in the rare earth oxides are selected from one or more rare earth elements other than lanthanum; the average particle size of the lanthanum slag is 5-30 mm; the green body is a cylinder with a bottom diameter of 100-300 mm and a height of 100-300 mm; (2) The smelting raw materials consisting of pre-baked material, second carbonaceous reducing agent and silica are smelted in an electric arc furnace at 1700-2200℃ for 3-8 hours to obtain alloy melt; (3) The alloy melt is cast into a mold to obtain a rare earth ferrosilicon alloy; The first carbonaceous reducing agent is selected from one or more of coke, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke; based on the fixed carbon contained in the first carbonaceous reducing agent, the amount of the first carbonaceous reducing agent is 20-30 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag. The second carbonaceous reducing agent is selected from one or more of coke, semi-coke, charcoal, gas coke, bituminous coal, and petroleum coke; based on the fixed carbon contained in the second carbonaceous reducing agent, the amount of the second carbonaceous reducing agent is 120-150 wt% of the theoretical amount of rare earth oxides contained in the reduced silica and lanthanum slag. The binder is selected from one or more of pulp, syrup, and plant starch; In the rare earth ferrosilicon alloy, the content of rare earth elements is 20-35 wt%, the content of silicon elements is 45-65 wt%, and the content of iron elements is 12-23 wt%.

2. The processing method according to claim 1, characterized in that, The average particle size of the first carbonaceous reducing agent is 5-30 mm, the average particle size of the second carbonaceous reducing agent is 5-30 mm, and the average particle size of the silica is 40-150 mm.

3. The processing method according to claim 1, characterized in that, The first carbonaceous reducing agent contains a fixed carbon content of ≥80 wt% and an ash content of ≤10 wt%. The second carbonaceous reducing agent contains a fixed carbon content of ≥80wt% and an ash content of ≤10wt%.

4. The processing method according to claim 1, characterized in that, The rare earth elements in the rare earth oxides are selected from one or more of samarium, europium, ytterbium, and thulium; The lanthanum slag contains less than or equal to 0.01 wt% calcium and less than or equal to 0.01 wt% lithium.

5. The processing method according to claim 1, characterized in that, The adhesive is used in the form of a colloid formed by mixing it with water.

6. The processing method according to claim 1, characterized in that, It also includes the following steps: The flue gas generated during the smelting process is treated to remove dust, and the dust in the flue gas is collected.

7. The processing method according to claim 1, characterized in that, In the rare earth ferrosilicon alloy, the total content of silicon and iron is 65-80 wt%.

8. The processing method according to claim 1, characterized in that, The rare earth silicon-iron alloy contains 17–32 wt% lanthanum.

Citation Information

Patent Citations

  • Method for producing rare earth ferrosilicon alloy by using rare earth slag

    CN116426773A